Risk of asthma in individuals with eosinophilic esophagitis: Population‐based cohort study with sibling analyses - Niki Mitselou; Amiko Uchida; Bjorn Roelstraete; Erik Melén; John J. Garber; Jonas F. Ludvigsson (Clinical and Translational Allergy)
Abstract Introduction There are limited data on the relationship between eosinophilic esophagitis (EoE) and asthma. We aimed to assess the risk of asthma in EoE patients compared with matched controls and siblings. Methods Through the ESPRESSO study, a Swedish nationwide population‐based histopathology cohort, we identified EoE patients diagnosed between 1989 and 2017 (n = 1146) and up to 5 age‐ and sex‐matched controls (n = 5022). Cox regression generated hazard ratios (HRs) for developing asthma. We compared EoE patients with sibling controls. Results The median age at EoE diagnosis was 42 years. During a median follow‐up of 3.8 years, 140 EoE patients (28.1/1000 person‐years) and 174 controls (7.2/1000 person‐years) developed asthma (HR = 3.96; 95% confidence interval [CI] = 3.16–4.96, p < 0.001). An increased risk of asthma was seen in the first 10 years after EoE diagnosis but not thereafter. EoE patients diagnosed in childhood or young adulthood were at a particularly high risk of asthma (HR = 4.74; 95% CI = 2.93–7.67, p < 0.001 and HR = 5.84; 95% CI = 3.68–9.29, p < 0.001, respectively). Compared with their non‐EoE siblings, EoE patients were at a 5‐fold increased risk of asthma (HR = 4.97; 95% CI = 3.13–7.92, p < 0.001). Conclusion EoE patients are at an increased risk of asthma compared with the general population, which is unlikely to be entirely explained through unmeasured intrafamilial factors given that the positive association remained in sibling analyses. Physicians caring for EoE should have a high awareness of concomitant asthma.